2021
DOI: 10.1371/journal.pcbi.1009596
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the molecular mechanism of the cancer formation by chromosome structural dynamics

Abstract: Cancer reflects the dysregulation of the underlying gene network, which is strongly related to the 3D genome organization. Numerous efforts have been spent on experimental characterizations of the structural alterations in cancer genomes. However, there is still a lack of genomic structural-level understanding of the temporal dynamics for cancer initiation and progression. Here, we use a landscape-switching model to investigate the chromosome structural transition during the cancerization and reversion process… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 142 publications
(197 reference statements)
1
15
0
Order By: Relevance
“…The compartment A/B can be quantified with +1 and −1 (epigenetic quantity) in this study (see Figure 5), which is similar to the positively charged and negatively charged residues of a polyampholyte chain. [ 56–58 ] We found that there are much more loci with low local CFI values (or low gene expressions) have −1 epigenetic quantity than those with high local CFI values (or high gene expressions). Then in order to make clear comparison, we calculated the distribution of the epigenetic quantity on the gene expressions.…”
Section: Resultsmentioning
confidence: 87%
See 4 more Smart Citations
“…The compartment A/B can be quantified with +1 and −1 (epigenetic quantity) in this study (see Figure 5), which is similar to the positively charged and negatively charged residues of a polyampholyte chain. [ 56–58 ] We found that there are much more loci with low local CFI values (or low gene expressions) have −1 epigenetic quantity than those with high local CFI values (or high gene expressions). Then in order to make clear comparison, we calculated the distribution of the epigenetic quantity on the gene expressions.…”
Section: Resultsmentioning
confidence: 87%
“…Moreover, the sequence charge decoration (SCD) value can reveal the property of the monomer distribution (SCD=1Ni=1Nj=i+1Nαiαjji$\mathrm{SCD} = \frac{1}{N}\sum \nolimits _{i = 1}^N {\sum \nolimits _{j = i + 1}^N {{\alpha _i}{\alpha _j}\sqrt {j - i} } }$). [ 56,58 ] The value of α is assigned according to the compartment or local CFI. SCD with large absolute value implies the sequence with charge‐blocky pattern, SCD with small absolute value implies the sequence with charge‐scrambled pattern (see sv15 and sv1 sequences in ref.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations